CGX, a standardized herbal syrup, inhibits colon-liver metastasis by regulating the hepatic microenvironments in a splenic injection mouse model - Lee, Sung-Bae; Hwang, Seung-Ju; Son, Chang-Gue (Frontiers in Pharmacology, 2022)
Background: Colon-liver metastasis is observed in approximately 50% of patients with colorectal cancer and is a critical risk factor for a low survival rate. Several clinical studies have reported that colon-liver metastasis is accelerated by pathological hepatic microenvironments such as hepatic steatosis or fibrosis. Chunggan syrup (CGX), a standardized 13-herbal mixture, has been prescribed to patients with chronic liver diseases, including fatty liver, inflammation and fibrotic change, based on preclinical and clinical evidence. Aim of the study: In the present study, we investigated anti-liver meta-static the effects of CGX in a murine colon carcinoma (MC38)-splenic injection mouse model. Materials and methods: C57BL/6N mice were administered with CGX (100, 200 or 400 mg/kg) for 14 days before or after MC38-splenic injection under normal and high-fat diet (HFD)-fed conditions. Also, above experiment was repeated without MC38-splenic injection to explore underlying mechanism. Results: The number of tumor nodules and liver weight with tumors were sup-pressed by preadministration of CGX in both normal and high-fat diet-fed mice. Regarding its mechanisms, we found that CGX administration significantly activated epithelial-cadherin (E-cadherin), but decreased vascular endothelial-cadherin (VE-cadherin) in hepatic tissues under MC38-free conditions. In addition, CGX administration significantly reduced hepatic steatosis, via modulation of lipolytic- and lipogenic-molecules, including activated adenosine monophosphate-activated protein kinase (AMPK) and peroxisome proliferator-activated receptor-alpha (PPARα). Conclusion: The present data indicate that CGX exerts an anti-colon-liver metastatic property via modulation of hepatic lipid-related microenvironments.